Literature review: Impact of Implementing Hospital-Based Health Technology Assessment (HB-HTA) in Hospital - Yohanes Mario Vianney; Chriswardani Suryawati; Martha Irene Kartasurya (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Hospital-based health technology assessment (HB-HTA) is very beneficial for the use of hospital medical technology, cost management, quality improvement, and protection of patient safety, and its usage is rising daily around the world. The main challenge of modern hospitals is purchasing medical technologies. Hospital-based health technology assessments (HB-HTAs) are used in healthcare facilities around the world to support management boards in providing relevant technologies for patients. Although some jurisdictions have used local/hospital-based HTA for more than two decades, little is known about its impacts and influence on hospital budgets, clinical practices, and patient outcomes. We performed a review using a mixed-methods approach with the goal of synthesizing existing information about the impacts and impact of community/hospital-based care. This study uses a narrative review, with many articles on the same topic. Articles were taken from the Scopus, Science Direct, ProQuest, SpringerLink, Google Scholar, Nature, JSTOR, and Emerald Insight databases with a total of 19 articles used. The purpose of this study was to determine does the implementation of HB-HTA in hospitals have a good impact on the progress of the hospital, and also discuss what are the benefits that will be obtained if implementing HB-HTA in hospitals.  Abstrak: Penilaian teknologi kesehatan berbasis rumah sakit (HB-HTA) sangat bermanfaat untuk penggunaan teknologi medis rumah sakit, manajemen biaya, peningkatan kualitas, dan perlindungan keselamatan pasien, dan penggunaannya meningkat setiap hari di seluruh dunia. Tantangan utama rumah sakit modern adalah membeli teknologi medis. Penilaian teknologi kesehatan berbasis rumah sakit (HB-HTA) digunakan di fasilitas kesehatan di seluruh dunia untuk mendukung dewan manajemen dalam menyediakan teknologi yang relevan bagi pasien. Meskipun beberapa yurisdiksi telah menggunakan HTA berbasis lokal/rumah sakit selama lebih dari dua dekade, sedikit yang diketahui tentang dampak dan pengaruhnya terhadap anggaran rumah sakit, praktik klinis, dan hasil pasien. Kami melakukan tinjauan menggunakan pendekatan metode campuran dengan tujuan mensintesis informasi yang ada tentang dampak dan dampak perawatan berbasis komunitas/rumah sakit. Penelitian ini menggunakan review naratif, dengan banyak artikel dengan topik yang sama. Artikel diambil dari database Scopus, Science Direct, ProQuest, SpringerLink, Google Scholar, Nature, JSTOR, dan Emerald Insight dengan total 19 artikel yang digunakan. Tujuan dari penelitian ini adalah untuk mengetahui apakah penerapan HB-HTA di rumah sakit berdampak baik bagi kemajuan rumah sakit, dan juga membahas apa saja manfaat yang akan diperoleh jika penerapan HB-HTA di rumah sakit.